The discovery of a data-driven causal diagram of sport participation in children and adolescents with heart disease: a pilot study - Gąsior, Jakub S.; Młyńczak, Marcel; Williams, Craig A.; Popłonyk, Aleksandra; Kowalska, Daria; Giezek, Paulina; Werner, Bożena (Frontiers in Cardiovascular Medicine, 2023)
Interventions aimed at improving physical activity (PA) levels in children and adolescents with heart disease did not produce expected outcomes. Safe participation in sport activities proposed based on actual recommendations could be a solution to promote PA in this population. The aims of this study were to discover a causal diagram of sport participation in children and youth with heart disease and establish factors affecting and affected thereof from the questionnaires, and then also to assess diagram reliability qualitatively in comparison to medical knowledge. Greedy Fast Causal Inference (GFCI) method was used for data-driven search of the directed acyclic graph representing causal relationships in the provided observational data. This causal discovery was performed using Tetrad software. A total of 121 completed questionnaires received from Caucasian patients (50 females) diagnosed with heart disease with age range 8-17 years were analyzed. Sport participants presented significantly higher values of health related quality of life (QoL) and motives for participating in physical and leisure activities. Age appears to be a cause of sport participation. Sport participation appears to be a cause of physical education classes participation what appears to be a cause of higher enjoyment. Higher enjoyment appears to be a cause of other motives for participating in physical and leisure activities but also a higher physical health score. The causal diagram provided a graphical representation of the causal relationship between sport participation and better QoL with potential confounders for children and adolescents with heart disease that nearly coincided with the existing literature. Clinical trials should be designed to validate clinical utility of the presented causal diagram.